Measurement of Empathy in Virtual Reality with Head-Mounted Displays A Systematic Review - Lee, Yongho (IEEE transactions on visualization and computer graphics, 2024)
We present a systematic review of 111 papers that measure the impact of virtual experiences created through head-mounted displays (HMDs) on empathy. Our goal was to analyze the conditions and the extent to which virtual reality (VR) enhances empathy. To achieve this, we categorized the relevant literature according to measurement methods, correlated human factors, viewing experiences, topics, and participants. Meta-analysis was performed based on categorized themes, and under specified conditions, we found that VR can improve empathy. Emotional empathy increased temporarily after the VR experience and returned to its original level over time, whereas cognitive empathy remained enhanced. Furthermore, while VR did not surpass 2D video in improving emotional empathy, it did enhance cognitive empathy, which is associated with embodiment. Our results are consistent with existing research suggesting differentiation between cognitive empathy (influenced by environmental factors and learnable) and emotional empathy (highly heritable and less variable). Interactivity, target of empathy, and point of view were not found to significantly affect empathy, but participants' age and nationality were found to influence empathy levels. It can be concluded that VR enhances cognitive empathy by immersing individuals in the perspective of others and that storytelling and personal characteristics are more important than the composition of the VR scene. Our findings provide guiding information for creating empathy content in VR and designing experiments to measure empathy